Pretreatment with rivaroxaban attenuates stroke severity in rats by a dual antithrombotic and anti-inflammatory mechanism - Dittmeier, Melanie; Kraft, Peter; Schuhmann, Michael K.; Fluri, Felix; Kleinschnitz, Christoph (Thrombosis and Haemostasis, 2016)
Stroke outcome is more favourable in patients receiving oral anticoagulants compared with non-anticoagulated patients. The reasons for this “stroke-attenuating” property of oral anticoagulants are largely unknown. This study examined whether prestroke anticoagulation with rivaroxaban, a novel direct factor Xa inhibitor, influences stroke severity, thrombin-mediated intracerebral thrombus formation and pro-inflammatory processes in a rat model of brain ischaemia/reperfusion injury. Male Wistar rats were anticoagulated with rivaroxaban and subjected to 90 minutes of transient middle cerebral artery occlusion. Infarct size, functional outcome and the occurrence of intracranial haemorrhage (ICH) were assessed until day 7. Thrombin generation was determined by measuring the amount of thrombin/antithrombin complex. Intracerebral thrombus formation was evaluated by histology and Western blot. CD68-immunoreactivity and the expression of cytokines and adhesion molecules were investigated to assess postischaemic inflammation. The integrity of the blood–brain barrier was analysed using fluorescein isothiocyanate-dextran. Rats pretreated with rivaroxaban developed significantly smaller strokes and less severe functional deficits compared with controls. Although rivaroxaban strongly reduced thrombin-mediated thrombus formation, this was not accompanied by an increased risk of ICH. In addition, rivaroxaban dampened the inflammatory response in the ischaemic brain by downregulating ICAM-1 expression and the activation of CD68+-immune cells. In contrast, rivaroxaban had no effect on the integrity of the blood–brain barrier after stroke. Here, we identified reduced thrombo-inflammation as a major determinant of the stroke-protective property of rivaroxaban in rats. Further studies are needed to assess the therapeutic potential of novel oral anticoagulants in the acute phase after a stroke.
Keywords: tMCAO; experimental stroke; rivaroxaban; thrombin; cerebral inflammation